EFFECT OF AMBON BANANA CONSUMPTION TO DECREASE BLOOD PRESSURE IN PREGNANT WOMAN WITH PREECLAMPS - Ira Pujiani; Ima Nurapriyanti; Melyana Nurul Widyawati; Elisa Ulfiana (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Preeclampsia greatly affects maternal and fetal mortality and morbidity being dependent on gestational age at the time of preeclampsia. Maternal mortality in Indonesia is still marked by three major causes of death: haemorrhage, hypertension in pregnancy (HDK) and infection. Method: This research used analytic survey method with experimental research design. The research design used prepost control design. The sample used was 20 pregnant women with pre-eclampsia, of which 10 were treated and 10 were controls. Result: The result of T-Test paired showed that the effect of the use of ambon banana in the systolic blood pressure treatment group was 0.0001 (P <0.05) and diastole was 0. 031 (p <0.05). Similarly, in systole the effect of banana utilize on the decrease in systolic blood pressure in groups was 0.101 (p>0.05) and in diastole 0.445 (p>0.05).